Educação ambiental no Ensino de Ciência: formação, prática e transversalidade - Afonso, Tatyanna de Melo (2011)
The teaching of science has shown many contemporary challenges to educators, especially in the complexity that is part of global society and the relationship of this with the teaching practices. The disciplinary fragmentation and disconnection with reality suggest concerns and questions about the continuing education of the teacher in front of the emerging paradigms. Considering that the speed of scientific and technological development requires the formation of individuals who follow and understand the flow of these transformations, clothed with moral and ethical values and articulate collectively. Within these situations, this research aimed to investigate about the process of continuing education of science teachers in municipal schools for the practice of mainstreaming at school, and the insertion of the Environmental Thematic Cross, in order to propose a course of continuing education teachers to strengthen the development of environmental education and optimization of Science Teaching in schools of Manaus. In this perspective, the research was situated in the Professional Development Division of the Magisterium - PMDD - City Department of Education Manaus - SEMED - to investigate the training context. Meanwhile, it was considered the practice of mainstreaming, in particular the approach of the Thematic Environmental Cross as promoters of an interdisciplinary process, promoting the transformation of educational practice and improving the quality of education. Consequently, the formation of critical and socially integrated individuals. In response, the continuing education of teachers, under the transversal perspective, teachers should allow the breaking of old paradigms, understanding and interpretation of reality and weaving with this curriculum. The research was based on the methodology of mixed methods, the dialectical conception of education and the results were tabulated and analyzed quantitatively and qualitatively, through Likert scale for some questions. Therefore, we prepared a proposal for intervention, called the Continuing Education Course on Environmental Thematic Cross for science teachers the final years of elementary schools of the city of Manaus, in order to reframe the teaching and training practices, pointing to the Cross Thematic Environmental axis as legitimizing the process of developing environmental education in public schools.